Representation of national cultural codes in K. Cvirka’s novel «Wolf island» - Duktava, Liubou G. (Journal of the Belarusian State University. Philology, 2023)
National cultural codes have an artistic embodiment in the images, motifs of the work, act as a kind of catalysts for showing the author’s position and forming certain views of the readers on the topics covered in K. Cvirka’s novel «Wolf island». Through the definition of cultural meanings within the dyads good – bad, right – wrong, masculine – feminine, history – eternity, and own – foreign, the work shows the relationship to the family, homeland, work, connection between man and society. It was concluded that in K. Cvirka’s novel «Wolf island», the spatial, temporal and personal codes are aimed at showing relations to native land, the action code helps to outline the specifics of the village life of a Belarusian, his hard work. When portraying the fate of Ignas Karalenja, the features of the attitude of residents living on Belarusian land to the motherland, family and their home are shown.
Keywords: cultural code; national image of the world; novel; cultural meaning; spatial code; time code